Bottom-up design of photoactive chiral covalent organic frameworks for visible-light-driven asymmetric catalysis - He, Ting (2023)
The development of chiral covalentorganic framework catalysts (CCOFs) to synthesize enantiopure organic compounds is crucial and highly desirable in synthetic chemistry. Photocatalytic asymmetric reactions based on CCOFs are eco-friendly and sustainable while they are still elaborate. In this work, we report a general bottom-up strategy to successfully synthesize several photoactive CCOFX (X = 1-5 and 1-Boc). The photoactive porphyrin building blocks are selected as knots and various secondary-amine-based chiral catalytic centers are immobilized on the pore walls of CCOFX through a rational design of benzoimidazole linkers. The porphyrin units act as light-harvesting antennae to generate photo-induced charge carriers for the activation of bromide during the photocatalytic asymmetric alkylation of aldehydes. Meanwhile, various aldehydes are activated by the chiral secondary amine to form the target products with a high yield (up to 97%) and ee value (up to 93%). The results significantly expand the scope to predesign CCOF photocatalysts for visible-light-driven asymmetric catalysis.